▼Liraglutide for type 2 diabetes?. Issue 5 (6th May 2010) - Unknown
Abstract : Several drugs that act on the incretin hormonal system are now licensed in the UK as add-on therapy for patients with type 2 diabetes mellitus and inadequate glycaemic control.1 ▼Liraglutide (Victoza – Novo Nordisk) is a recently licensed long-acting glucagon-like peptide-1 (GLP-1) mimetic that can be given once daily as a subcutaneous injection, as part of either dual or triple therapy.2 Advertising claims that use of the drug leads to "reductions in weight"; "reductions in systolic blood pressure"; and "improvements in β-cell function", as well as reductions in blood glucose concentrations. Here we assess the evidence for these claims and consider whether liraglutide has a role in the management of patients with type 2 diabetes.